MODEL DIGITAL STORYTELLING DALAM PEMBELAJARAN BAHASA ARAB MELALUI YOUTUBE 'BELAJAR BAHASA ARAB DARI NOL - Akmal Varras Amrulloh Akmal Varras; Alfina Arofatul B Alfina; Denmas Azkal Basyari Arsyad Denmas (SPESIFIK: Jurnal Pendidikan dan Pembelajaran, 2026)
This study examines the application of the Digital Storytelling (DST) model in Arabic language learning, focusing on the video "Belajar Bahasa Arab dari Nol" (Learning Arabic from Scratch) by Mustaqiem Alkierinjiyy on the YouTube platform. The DST model combines narration, visualization, and interactive methods to enhance understanding of basic Arabic, including letter recognition, word formation, and grammar (nahwu and sharaf). The main aim of this study is to evaluate the effectiveness of DST in helping beginner learners. The results of the study indicate that the implementation of DST enhances student engagement, particularly through interactive activities such as repetition of pronunciation and writing Arabic letters. Additionally, the flexibility of YouTube access makes it easier for learners to follow the material anytime and anywhere. However, the study also notes that the primary challenge is the limitation of internet infrastructure, which affects video accessibility, especially in areas with unstable internet connections. This study concludes that YouTube-based DST can be an effective and enjoyable method for Arabic language learning, especially for beginners, due to the combination of interactivity and media flexibility.